The «native — stranger» opposition in perception of national identity of inhabitants of North America - Шостак, О. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The purpose of this article was to develop comprehensive historic framework of the opposition “Self” and “the Other” during the formation of Native American identity with a primary focus upon the tension between covert symbolic convergence of two worlds’ outlook systems and mainstream America’s appropriation of aboriginal cultural features as an inevitable act of colonization.